The Evolution of Corporate Criminal Liability in Indonesia: A Theoretical and Comparative Analysis of Judgment No. 1405 K/Pid.Sus/2013 and the 2023 Criminal Code (International Journal of Applied Research and Innovation, 2026)
This study examines the evolution of corporate criminal liability in Indonesia through a theoretical and comparative analysis of Supreme Court Decision Number 1405 K/Pid.Sus/2013 and the regulatory framework introduced by Law Number 1 of 2023 concerning the Indonesian Criminal Code. The research aims to analyze how the construction of corporate liability has developed from a model centered on individual attribution of fault toward a more systemic and organizational form of responsibility. This study employs normative legal research with statutory, conceptual, and case approaches. The primary legal materials include the Supreme Court decision and relevant statutory provisions governing corporate criminal liability, while secondary materials consist of scholarly articles and legal literature discussing modern corporate liability doctrines. The findings show that the Supreme Court decision still relies on identification theory, where the actions and intentions of corporate managers are attributed to the corporation. In contrast, the 2023 Criminal Code introduces broader parameters of liability, including failure to prevent, omission, and control by beneficial owners. This shift reflects a significant transformation toward organizational liability, strengthening the effectiveness of criminal law enforcement against corporate crimes in Indonesia